Mechanism of notable difference in the field delay times of no-insulation layer-wound and pancake-wound REBCO coils. (19th August 2016) - Suetomi, Y; Yanagisawa, K; Nakagome, H; Hamada, M; Maeda, H; Yanagisawa, Y
Abstract: The characteristic magnetic field delay time for a no-insulation (NI) REBCO layer-wound coil is three orders of magnitude longer than that for a NI REBCO double-pancake coil. In a NI layer-wound coil, the circumferential current firstly flows along the periphery of the coil winding, and then it diffuses from the top and bottom turns into the middle turns of the winding, resulting in a long characteristic magnetic field delay time due to the current diffusion process. In contrast, the characteristic magnetic field delay time for a NI double-pancake coil is dominated by the circumferential current decay in individual turns. On the basis of a derived scaling law, the characteristic magnetic field delay time for a NI REBCO layer-wound coil for a 400 MHz LTS/REBCO nuclear magnetic resonance (NMR) magnet is 37 h, while that for a NI REBCO double-pancake coil is only <1 min. Thus, it is demonstrated that a double-pancake-winding is greatly preferred to a layer-winding for NMR applications from the view point of the characteristic magnetic field delay time.